Management Of Consumer Behavior Patterns Based On Marketing Strategies (Eurasian Scientific Herald, 2025)
On the basis of models of consumer behavior, the features of the tasks of marketing services are analyzed. Based on the modeling of consumer behavior, it is possible to find out what needs are met by the services provided on the market, and, if necessary, improve their characteristics, in addition, the classification of approaches to modeling consumer behavior is analyzed